Masculinization of silver perch (bidyanus bidyanus mitchell 1838) by dietarysupplementation of 17 a-methyltestosterone - Sulaeman; Fotedar, R. (Elsevier BV, 2017)
The aim of this research was to assess the possible use of dietary supplementation of 17a-methyltestosterone (MT), to produce all-male population of silver perch, Bidyanus bidyanus Mitchell 1838, as a step forward in producing neomales, which later can be used to produce an all-female population. Larvae were fed 17a-MT at various concentrations, viz. 0 (control), 9 and 18 mg/kg diet for the period of 30 days from 31 to 60 days post hatching (dph). Phenotypic sex ratios at 225 dph identified through histological examination revealed that MT significantly (P < 0.05) increases the male percentage from 59% to 100%. Testes of MT-fed fish were well developed, had a normal appearance at the same developmental stages to that of the control group. No significant differences (P > 0.05) in gonad weight (GW), gonad length (GL) and gonadosomatic index (GSI) among treatments which may indicate that the resulting neomales were viable. The MT supplementation did not influence the mortality rate, but significantly (P < 0.05) increased the final weight and specific growth rate (SGR). The study suggests that the dietary supplementation of MT at 9–18 mg/kg of the diet from 31 to 60 dph larvae is effectively in inducing masculinization in silver perch.